Perception of Library Personel Towards Socal Media Utilization for Information Service Delivery in University Libraries in Kwara State - saliu, abdulfatai; AKINBOWALE , Aishat Temitope (International Journal of Knowledge Content Development & Technology, 2024)
The study examined perception of library personnel towards social media utilization for information service delivery in kwara state university library. It adopted the descriptive survey design with population consisting of 27 professional librarians in three selected university libraries in kwara State. Total enumerative sampling techniques were used because the population of the study is manageable by the researcher. Percentage and mean were used in analyzing the data. Primary data solicited would be cleaned, coded and entered into the Statistical Package for Social Sciences (SPSS) version 20 software for quantitative analysis. The findings of the study revealed the services rendered by library professional in university libraries in Kwara State, are Current Awareness Services (CAS), Photocopying services, Technical Services, Circulation/borrowing services, Internet services, and Bibliographic verification services. Majority of the respondent indicated Myspace, Google plus, Flickr, Telegram, Twitter, WhatsApp and Facebook are the social media platforms used for service delivery by librarians. Also, majority of the respondents in university libraries indicated Google plus, LinkedIn, Myspace, Skype, WhatsApp, Flickr, WeChat, Twitter and Facebook as social media space use for information service delivery effectively and Bandwidth problem, Limited fund, Lack of maintenance culture, Lack of Awareness, Copyright Issue, Technophobia are the major challenges inhibiting the use of social media for service delivery by the library staff. Lastly, the study concluded with recommendations.